2016
DOI: 10.1007/s00005-016-0436-4
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of the ERAP1 Gene and Risk of NSCLC: A Comparison of Genetically Distant Populations, Chinese and Caucasian

Abstract: An effective cytotoxic immune response to neoplastic cells requires efficient presentation of antigenic peptides to T lymphocytes by HLA class I (HLA-I) molecules. The HLA-I-bound peptide repertoire depends on antigen-processing machinery molecules. Aminopeptidase residing in endoplasmic reticulum 1 (ERAP1) trims peptides to the optimal length for HLA-I binding. Single nucleotide polymorphisms (SNPs) in the ERAP1 gene result in changes in aminopeptidase activity and specificity. This may affect susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
1
21
1
Order By: Relevance
“…This may explain the association between SNPs in ERAP genes and autoimmune and infectious diseases (23)(24)(25)(26). Similarly, in human cancers, our previous study and other studies have reported associations between polymorphisms in ERAP genes and human cancers (27)(28)(29)(30)).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…This may explain the association between SNPs in ERAP genes and autoimmune and infectious diseases (23)(24)(25)(26). Similarly, in human cancers, our previous study and other studies have reported associations between polymorphisms in ERAP genes and human cancers (27)(28)(29)(30)).…”
Section: Introductionsupporting
confidence: 67%
“…As components of the APM, ERAP1 and ERAP2 are important determinants of the repertoire of peptides ultimately presented by HLA class I molecules (34)(35)(36)(37). Our previous study showed that four polymorphisms in ERAP1 are associated with non-small cell lung cancer in a Chinese population (27). In the current study, we selected six SNPs in ERAP1 and five SNPs in ERAP2, and investigated their distribution in CIN patients, cervical cancer patients, and healthy individuals.…”
Section: Discussionmentioning
confidence: 94%
“…Since ERAP activity could be influenced by the various polymorphisms that these enzymes have, we analyzed the ERAP1 alleles present in the investigated cell lines. Amongst others, we observed two described polymorphisms associated with the risk of cancer development . The R127P polymorphism in HeLa, UKRV‐Mel‐15a and Ma‐Mel‐63a and the Q730E mutation in Ma‐Mel‐86a cells suggest an altered peptide trimming activity in the latter (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…). We could detect two ERAP1 polymorphisms (R127P and Q730E), which are correlated with an increased risk of cancer development . However, only the Q730E mutation has been shown to display reduced peptide trimming activity suggesting an impaired gp100 209‐217 epitope generation in melanoma cells expressing the Q730E variant .…”
Section: Discussionmentioning
confidence: 95%
“…In “KIR and cancer” session, chaired by Lorenzo Moretta and Markus Uhrberg, Piotr Kusnierczyk presented data about ERAP1 , ERAP2 , KIR , and HLA class I polymorphisms in a non‐small‐cell lung cancer (NSCLC) cohort including Polish and Chinese patients. He found highly significant differences between patients and controls in ERAP1 genotype frequencies in Chinese but not in Poles, probably because of the highly significant differences in ERAP1 / 2 SNP genotype frequencies between these two populations . No correlation among individual KIR genes with NSCLC susceptibility was detected.…”
Section: Kir In Diseases and Cancermentioning
confidence: 98%